Genetic and metabolic engineering approaches for enhanced biodesulfurization of petroleum fractions - Bagchi, Asheemita; Srivastava, Preeti (Frontiers in Bioengineering and Biotechnology, 2024)
Sulfur, an abundant component of crude oil, causes severe damage to the environment, poses risks to human health, and poisons the catalysts used in combustion engines. Hydrodesulfurization, the conventionally used method, is not sufficient to remove thiophenes like dibenzothiophene (DBT) and other aromatic heterocyclic compounds. The push for “ultra-clean” fuels, with sulfur content less than 15 ppm, drives the need for deep desulfurization. Thus, in conjunction with hydrodesulfurization, efficient and eco-friendly methods of deep desulfurization, like biodesulfurization, are desirable. In biodesulfurization, naturally desulfurizing microorganisms are used, with genetic engineering and biotechnology, to reduce the sulfur content of crude oil to below 15 ppm. In this review, we describe genetic and metabolic engineering approaches reported to date to develop more efficient methods to carry out biodesulfurization, making it a practically applicable reality.